Penggunaan music sebagai alat pendukung pembelajaran bahasa Inggris - Anggita Pebrianti (Universitas Muhammadiyah Muara Bungo, 2022)
English is the international language most widely used for communication. Learning English is something that must be learned in this modern era. The learning process also plays an important role in the acquisition of the language. The school requires additional English lessons due to the lack of teaching hours from local teachers. The needs of the children at the school are something that must be resolved because English learning must be improved for students. The presence of English teachers at school will really help the early learning process of a foreign language, especially if the teacher can teach English in various ways. There are many ways that can be used to improve students' learning abilities, learning through songs can be used in this process. Learning English through songs can be an effective means of improving students' memory and ability in learning English, this can be proven by the ease with which students can follow and remember songs.